2019
DOI: 10.1021/acs.jpcc.8b12554
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Carbon Nanotubes from Oxidation for Selective Carbon Impurity Elimination

Abstract: Purity of carbon nanotubes (CNTs) is essential to avoid a dramatic decrease in their performances. In addition to metallic impurities, carbonaceous impurities have been shown to be responsible for pronounced effects. However, they are highly difficult to be selectively removed from CNT samples because of the similar chemical reactivity of these two kinds of carbon species. The existing purification methods often lead to high CNT consumption (>90 wt %). The proposed method consists of a one-pot gas-phase treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…The oxygen content is roughly in the 0.5-1 at.% range for the raw and the treated samples. As already reported from our previous works, [25,33] chlorine could be detected in MWCNTs purified by the chlorine-based method. For both pCl1 and pCl2, the Cl 2p feature typically shows two components (each consisting of the 3/2 and 1/2 level with a spin-orbit splitting of 1.6 eV) as shown in Figure S3 (Supporting Information).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The oxygen content is roughly in the 0.5-1 at.% range for the raw and the treated samples. As already reported from our previous works, [25,33] chlorine could be detected in MWCNTs purified by the chlorine-based method. For both pCl1 and pCl2, the Cl 2p feature typically shows two components (each consisting of the 3/2 and 1/2 level with a spin-orbit splitting of 1.6 eV) as shown in Figure S3 (Supporting Information).…”
Section: Resultssupporting
confidence: 79%
“…Interestingly, the sublimation temperature of the metal‐based impurities can be significantly reduced in the 800–1200 °C range after their facile reaction with halogens such as bromine [22] or chlorine [23,24] . Moreover, since halogens are advantageously poorly reactive with carbon, the CNTs can hence be preserved or even protected by such treatments [25] . We have already applied such chlorine‐based purification to single walled CNTs (SWCNTs) from several sources and double‐walled CNTs (DWCNTs) with good purification yields [13,23,26–28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it has been shown that the use of a mixture of H 2 O 2 and a non-oxidizing acid such as HCl combined with ultrasonication and high temperature treatments is an effective way of removal of amorphous carbon and dissolving the catalyst residues without changing the surface chemistry of CNTs. 22,23 Gas-phase oxidative processes such as annealing in air and/or O 2 , 24 CO 2 , 25 Cl 2 /O 2 mixture, 26 and steam 27 can also be implemented to selectively remove carbonaceous impurities due to their lower stability than the CNT structure. However, this process should be done with care as defects and inorganic residues can decrease the decomposition temperature of CNTs.…”
Section: Challengesmentioning
confidence: 99%
“…Jeung et al 23 used chloroform (CHCl 3 ) as a gas-phase purification approach to obtain metal-free MWCNTs, while it had no effect on carbon-based impurities. Nawal et al 24 reported a one-pot gas-phase treatment combining chlorine and oxygen. This method can remove both metallic and carbon impurities, however it also resulted in chlorine-containing functional groups present on the wall of CNTs.…”
Section: Introductionmentioning
confidence: 99%